2020
DOI: 10.3389/fenvs.2020.559195
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-Solubilizing Fungi and Alkaline Phosphatase Trigger the P Solubilization During the Co-composting of Sorghum Straw Residues With Burkina Faso Phosphate Rock

Abstract: Phosphate rocks (PR), the primary source of phosphorus (P), are often co-composted with organic materials to enhance P availability. However, the mechanisms of P solubilization in PR-enriched composts are not well elucidated. This study investigated such mechanisms by monitoring the changes in P fractions during composting and by determining the relationships between the physicochemical and biological parameters. Sorghum straw residues were composted alone (Comp), or with 10% PR (P-Comp), or with 10% PR and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 75 publications
(78 reference statements)
0
16
0
1
Order By: Relevance
“…Therefore, the increased exchangeable cations in soils amended with P-Comp-Soil, particularly calcium and magnesium (data not shown), could be derived from the enhanced microbial-mediated phosphate solubilization during composting, concomitantly releasing more cations in the compost product and in soil. Sarr et al (2020) found in this type of compost a higher number of phosphate-solubilizing fungi and phosphatase-releasing microbial genes. Phosphate-solubilizing bacteria and fungi (Liu et Penicillium pinophilum has been shown to increase the phosphate availability in soil and the biomass yields of sorghum (Steiner et al 2016).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Therefore, the increased exchangeable cations in soils amended with P-Comp-Soil, particularly calcium and magnesium (data not shown), could be derived from the enhanced microbial-mediated phosphate solubilization during composting, concomitantly releasing more cations in the compost product and in soil. Sarr et al (2020) found in this type of compost a higher number of phosphate-solubilizing fungi and phosphatase-releasing microbial genes. Phosphate-solubilizing bacteria and fungi (Liu et Penicillium pinophilum has been shown to increase the phosphate availability in soil and the biomass yields of sorghum (Steiner et al 2016).…”
Section: Discussionmentioning
confidence: 57%
“…Pcompost-soil (P-Comp-Soil) was made by adding BPR and sorghum rhizosphere soil to the sorghum straw residues during the fabrication process. Sarr et al (2020) reported that the P-Comp-Soil contained 13% higher labile-P than the P-Comp. In the present study, the application rate of the organic materials (SS, Comp, P-Comp, P-Comp-Soil) was 1.34 t ha -1 .…”
Section: Experimental Design and Sorghum Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The PSM controls the phytopathogens attack by synthesizing pivotal molecules like siderophores ( Sarr et al, 2020 ), antibiotics ( Raaijmakers and Mazzola, 2012 ), lytic enzymes ( Herrera-Quiterio et al, 2020 ), cyanogenic compounds ( Munir et al, 2019 ), and through induction of systemic resistance (ISR; Audenaert et al, 2002 ). Due to this, the soil PSM improves the growth and grain yield of sorghum by suppressing the damaging impact of biotic stresses.…”
Section: Biotic Stress Alleviation By Psmmentioning
confidence: 99%
“…Currently, the use of phosphate-solubilizing microbes (PSMs) has been shown as a promising method since they play a key role in P dynamics in soil and the subsequent availability of this element to plants (Islam and Hossain, 2012;Kafle et al, 2019). PSMs fractionate insoluble P forms into soluble forms through various biological mechanisms, including the production of organic acids and extracellular enzymes, which convert insoluble forms of P into forms available for plant absorption (Hanif et al, 2015;Li et al, 2015;Baliah et al, 2016;Gurikar et al, 2016;Doilom et al, 2020;Sarr et al, 2020;Zúñiga-Silgado et al, 2020). The organic acids produced include glycolic, 2-ketogluconic, acetic, citric, propionic, succinic, tartaric, formic, fumaric, lactic, malic, butyric, gluconic, valeric, oxalic, and citric acids (Hwangbo et al, 2003;Chen et al, 2006;Patel et al, 2008;Scervino et al, 2010;Zhu et al, 2012;Jog et al, 2014;Mehta et al, 2015;Yadav et al, 2015).…”
Section: Introductionmentioning
confidence: 99%